Análise multitemporal da cobertura florestal da microbacia do Arroio Grande, Santa Maria, RS - Kleinpaul, Joel Juliano (2005)
This study had as objective to do a multi-temporal analysis from Arroio Grande watershed area, located in Santa Maria, RS, to detect the forest covering changes, its localization and quantification, as well as, to monitor the deforestation and regeneration processes and its main determinant factors. Four satellite images were used: LANDSAT 5 (1987), LANDSAT 5 (1995), LANDSAT 7 (2002) and CBERS 2 (2005). The SPRING applicative was used to elaborate the cartography dada basis and to digitally process the images. The images were segmented with threshold 10 to similarity and 20 to area and classified with Bhattacharya algorithm in the following land uses: forest, field, exposed soil, agriculture, irrigated agriculture and water lamina. After the images classification, a thematic maps cross was done with LEGAL programming. As a result, maps with the following land uses were obtained: forest maintenance, regeneration and deforestation. For a period of 18 years, the forest covering increased 25,59% or 10,24% in the area, mainly in the hillside and in the plateaus, changing from 14.135,42 ha (40,01%) in 1987 to 17.752,20 ha (50,25%) in 2005. However, there is still a great deficit of riparian forest in plain (depression), mainly due to rice cultivation. The obtained results show the potential of Remote Sensing and Geoprocessing techniques in mapping the land use. They also can be used to support researches, territorial planning, economical development and environmental preservation in this region. With the data bank obtained, it will be possible to create models able to simulate the forest covering dynamic in the studied area.